Meal-Related Asprosin Serum Levels Are Affected by Insulin Resistance and Impaired Fasting Glucose in Children With Obesity - Corica, Domenico; Pepe, Giorgia; Aversa, Tommaso; Currò, Monica; Curatola, Selenia; Li Pomi, Alessandra; Alibrandi, Angela; Ientile, Riccardo; Wasniewska, Malgorzata (Frontiers in Endocrinology, 2022)
Asprosin physiologically increases in fasting conditions and decreases with refeeding and has been implicated in glucose homeostasis. An alteration of meal-related circadian oscillation of asprosin has been suggested in adults affected by type 2 diabetes mellitus. Aims of this study were to test the hypothesis of an alteration in the meal-related variation of asprosin levels in non-diabetic children and adolescents with obesity and to assess which metabolic variables condition this variation in non-diabetic children and adolescents with obesity. This is a cross-sectional study which included 79 children and adolescents with obesity. Children underwent clinical and biochemical assessments, including oral glucose tolerance test (OGTT), and liver ultrasound evaluation. Asprosin serum levels were measured by an enzyme-linked immunosorbent assay at a fasting state and at the 120-minute OGTT timepoint (2h-postprandial asprosin). Fasting and 2h-postprandial asprosin serum levels did not significantly differ in the entire study population (374.28±77.23 vs 375.27±81.26;p=0.837). 55.7% of patients had a significant increase in 2h-postprandial asprosin compared with fasting levels. The asprosin level increase condition was significantly associated with HOMA-IR (OR,1.41; 95%CI,1.005-1.977; p=0.047), fasting glycaemia (OR,1.073; 95%CI,1.009-1.141;p=0.024) and HOMA-B (OR,0.99; 95%CI,0.984-0.999; p=0.035). Moreover, the IFG condition was associated with the increase in asprosin levels (OR, 3.040; 95%CI, 1.095-8.436; p=0.033), even after adjustment for HOMA-IR, BMI SDS, sex and pubertal stage. Insulin resistance and IFG influence meal-related changes of asprosin serum levels in our study population of obese, non-diabetic, children. Alteration of asprosin circadian secretion might be an early biomarker of impaired glucose regulation in obese children with insulin resistance.